ICTD state of the union: Where have we reached and where are we headed - Patra, R.; Pal, J.; Nedevschi, S. (2009 International Conference on Information and Communication Technologies and Development, 2009)
In this study we examine the history and growth of ICTD since the 1990s. We underline the trends defining this research field and examine the progress in research areas that have come to dominate discussion in ICTD through a thorough literature review of the last decade of ICTD work. In order to answer questions pertaining to the rigor, impact and significance of ICTD, and to compare the expectations and perceived achievements with respect to different development goals, we interview 50 expert ICTD researchers and practitioners. We analyze these results to understand stakeholders' opinions on the past performance of ICTD, both as an academic field and as an area of development practice, and identify defining ideas on the potential directions for the future of ICTD. This study is work in progress and we have continuing research in this area, the subset presented here is rigorous and ready for wider discussion.